Usability Design for the Unisbank Smart Campus Application Using Website-Based Usability Testing - Kurniawati, Detia; Sugiyamta, Sugiyamta (Jurnal Teknologi Sistem Informasi dan Aplikasi, 2024)
Smart Campus Unisbank is an application-based online platform used for tuition payment, course registration (KRS), viewing semester grades, and various other activities in the educational field. This research uses the analysis of reviews of the Smart Campus Unisbank application found on Google Playstore using the Usability Testing Method. Usability Testing is used to analyze display issues of an application to match the needs of the service users. This Usability Testing includes several components, including learnability, efficiency, memorability, errors, and satisfaction. Based on user reviews of the Smart Campus application available on Google Playstore, recommendations obtained will be implemented into the website. Complaints from students are visualized into a diagram design